Improvement of cancellous bone microstructure in patients on teriparatide following alendronate pretreatment - Fahrleitner-Pammer, Astrid; Burr, David; Dobnig, Harald; Stepan, Jan J; Petto, Helmut; Li, Jiliang; Krege, John H; Pavo, Imre (Bone, 2016)
An increase in procollagen type I amino-terminal propeptide (PINP) early after teriparatide initiation was shown to correlate with increased lumbar spine areal BMD and is a good predictor of the anabolic response to teriparatide. Few data exist correlating PINP and bone microstructure, and no data exist in patients on teriparatide following prior potent antiresorptive treatment. This exploratory analysis aimed to investigate the effects of teriparatide on cancellous bone microstructure and correlations of bone markers with microstructure in alendronate-pretreated patients. This was a post hoc analysis of changes in bone markers and three-dimensional indices of bone microstructure in paired iliac crest biopsies from a prospective teriparatide treatment study in postmenopausal women with osteoporosis who were either treatment-naïve (TN, n=16) or alendronate-pretreated (ALN, n=29) at teriparatide initiation. Teriparatide (20μg/day) was given for 24months; biopsies were taken at baseline and endpoint, and serum concentrations of PINP and type 1 collagen cross-linked C-telopeptide (βCTX) were measured at intervals up to 24months. In the TN and ALN groups, respectively, mean (SD) increases in three-dimensional bone volume/tissue volume were 105 (356)% (P=0.039) and 55 (139)% (P<0.005) and trabecular thickness 30.4 (30)% (P<0.001) and 30.8 (53)% (P<0.001). No significant changes were observed in trabecular number or separation. In the ALN patients, 3-month change of neither PINP nor βCTX correlated with indices of cancellous bone microstructure. However, 12-month changes in biochemical bone markers correlated significantly with improvements in bone volume/tissue volume, r=0.502 (P<0.01) and r=0.378 (P<0.05), trabecular number, r=0.559 (P<0.01) and r=0.515 (P<0.01), and reduction of trabecular separation, r=-0.432 (P<0.05) and r=-0.530 (P<0.01), for PINP and βCTX, respectively. We conclude that cancellous bone microstructure improved with teriparatide therapy irrespective of prior antiresorptive use.
Keywords: inhibitory kostní resorpce; Bone Density Conservation Agents; Cancellous bone microstructure; remodelace kosti; Humans; Bone Remodeling; lidé středního věku; kolagen typu I; trabekulární kostní tkáň; Osteoporosis, Postmenopausal; Teriparatide; Female; Aged; Alendronate pretreatment; Turnover markers; Collagen Type I; senioři; lidé; Alendronate; peptidy; Peptides; Peptide Fragments; alendronát; ženské pohlaví; postmenopauzální osteoporóza; prokolagen; Middle Aged; Bone Density; kostní denzita; peptidové fragmenty; Cancellous Bone; teriparatid; Procollagen; PINP